Adapting Interactive Interview Tasks to Remote Data Collection: Human Subjects Research That Requires Annotations and Manipulations of Chemical Structures During the COVID-19 Pandemic - Chatha, Courtney J; Bretz, Stacey Lowery (Journal of chemical education, 2020)
In response to the Coronavirus-19 pandemic, higher education institutions quickly moved to emergency remote learning, and most human subjects research came to an immediate halt. Chemistry education researchers who wanted to continue data collection were confronted by many challenges, including research designs and data collection methods that had presumed local access to student participants, such as interactive tasks for students to complete during face-to-face interviews. In order to resume data collection remotely, interactive tasks needed to be translated to a virtual space. This communication reports adaptations made to an interview protocol to facilitate data collection in a remote setting with students as they interacted with and annotated multiple representations of chemical structures. The benefits and limitations to remotely capturing students’ drawings and interactions with multiple chemistry representations using the features available through a common video conferencing platform are discussed.